Increase in human immunodeficiency virus 1 diversity and detection of various subtypes and recombinants in north‐eastern Brazil. Issue 4 (April 2017) - Lima, Kledoaldo; Leal, Élcio; Cavalcanti, Ana Maria Salustiano; Salustiano, Daniela Medeiros; de Medeiros, Luzidalva Barbosa; da Silva, Sirleide Pereira; Lacerda, Heloísa Ramos
Abstract : Purpose. : Diverse human immunodeficiency virus 1 (HIV‐1) subtypes and circulating recombinant forms are found in Brazil. The majority of HIV‐1 molecular epidemiological studies in Brazil have been conducted in the southern and south‐eastern regions of the country, although several recent studies in the north‐eastern region have addressed this issue. The objective of this study was to molecularly characterize HIV‐1 circulating in Pernambuco, north‐eastern Brazil. Methodology. : A total of 64 samples were collected from 2002 to 2003, and another 103 were collected from 2007 to 2009. The protease and partial reverse transcriptase regions of the HIV‐1 polymerase‐encoding ( pol ) gene were sequenced, and subtyping, recombination and phylogenetic analyses were performed. Results/Key findings. : Subtype B (60.9%) was found to be predominant, followed by HIV‐1 F (31.4%). Several BF recombinants (4.2%), and BC and AG recombinants were also identified. The intra‐subtype genetic diversity was estimated to be 0.065 (sd±0.004) for HIV‐1 B and 0.055 (sd±0.004) for HIV‐1 F, reflecting a greater accumulation of mutations in subtype B ( P <0.01). More codons were found to be under positive selective pressure in samples collected from 2007 to 2009, from individuals with a T‐cell count≥200 cells mm −3 and from women. Coalescence data indicated that the subtype F population has been continuously expanding. Conclusions. : HIV‐1 shows high genetic diversity in the state of Pernambuco. Thus, additional molecular evaluations of circulating strains will provide a better understanding of the epidemic and may lead to more effective preventive strategies.